Comparison of Multi Criteria Decision Making Method (WP, SAW & TOPSIS) for best supplier selection. - Sumanto Sumanto; Lita Sari Marita; Karlena Indriani; Lia Mazia; Ade Christian; Ruhul Amin (Seminar Nasional Informatika (SEMNASIF), 2021)
Purpose: This study aims to find the best method among the methods that have often been used in the selection of suppliers among the methods to be compared is the MCDM (WP, SAW &TOPSIS) method.Design/methodology/approach: Selecting the right supplier will significantly reduce the cost of purchasing materials and improve the competitiveness of the company. In Rouydel's research for supplier selection using 6 criteria that will be an assessment of supplier selection including: Quality, Price / cost, standardization, Service, Flexibility, On time delivery [8].Findings/result: The results of this study are that the three WP, SAW and TOPSIS methods can be used in supplier selection, of the three methods almost all are equal in the ranking so it can be concluded that the three WP, SAW and TOPSIS methods are the right methods in the decision making of the best supplier selection.Originality/value/state of the art: The selection of the best suppliers in Indonesia rarely pays attention to the Flexibility factor when this factor is needed in the selection of suppliers, and on average only based on price, shipping, quality criteria.